2022
DOI: 10.3399/bjgp.2022.0103
|View full text |Cite
|
Sign up to set email alerts
|

Change in treatment burden among people with multimorbidity: a follow-up survey

Abstract: Background: Treatment burden is the workload of being a patient and its impact on wellbeing. Little is known about change in treatment burden over time for people with multimorbidity. Aim: To quantify change in treatment burden, determine factors associated with this change, and evaluate a revised single-item measure for high treatment burden in older adults with multimorbidity. Design and setting: A 2.5-year follow-up of a cross-sectional postal survey via six general practices in Dorset, England. Method: GP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…Previous research about exploring variables being associated with a higher travel burden in patients with multimorbidity is very limited. Hounkpatin et al showed that patients with limited health literacy are especially at risk for having a high travel related treatment burden ( Hounkpatin et al, 2022 ). In addition, literature showed that the travel burden for patients with multimorbidity is especially straining to patients with deprived SES and to patients living in remote areas ( Rosbach & Andersen, 2017 ; Sav et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research about exploring variables being associated with a higher travel burden in patients with multimorbidity is very limited. Hounkpatin et al showed that patients with limited health literacy are especially at risk for having a high travel related treatment burden ( Hounkpatin et al, 2022 ). In addition, literature showed that the travel burden for patients with multimorbidity is especially straining to patients with deprived SES and to patients living in remote areas ( Rosbach & Andersen, 2017 ; Sav et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Literature has demonstrated the role of travel burden on health, as it is for example associated with a delay in cancer diagnosis, leading to more advanced disease at diagnosis, inappropriate treatment, worse prognosis and lower quality of life ( Ambroggi et al, 2015 ). Moreover, travel burden seems to be an important part of overall treatment burden for patients with multimorbidity ( Hounkpatin et al, 2022 ; Rosbach & Andersen, 2017 ). In a time of increasing treatment and travel burden of a growing patient population, it is worth noting that travel burden is something to be taken into account during treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…We will use the theoretical model established by Andersen and Newman to investigate the experience of the care system among patient participants 43. This model identifies three key types of factors that could influence the use of healthcare services: predisposing features (eg, age, sex, ethnicity, previous illnesses), enabling features (eg, income, access to care, employment) and needs (eg, symptoms, diagnosis, functioning) 17. Furthermore, participants will be encouraged to indicate any care they would have preferred to receive but did not, as well as suggest reasons or barriers for why this was the case.…”
Section: Methodsmentioning
confidence: 99%
“… 43 This model identifies three key types of factors that could influence the use of healthcare services: predisposing features (eg, age, sex, ethnicity, previous illnesses), enabling features (eg, income, access to care, employment) and needs (eg, symptoms, diagnosis, functioning). 17 Furthermore, participants will be encouraged to indicate any care they would have preferred to receive but did not, as well as suggest reasons or barriers for why this was the case. The removal of these barriers may have cost implications and could also impact outcomes, which we will explore using economic modelling methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation